Biotin‐thiamine responsive basal ganglia disease: Identification of a pyruvate peak on brain spectroscopy, novel mutation in SLC19A3, and calculation of prevalence based on allele frequencies from aggregated next‐generation sequencing data. Issue 6 (12th April 2017) - Ferreira, Carlos R.; Whitehead, Matthew T.; Leon, Eyby
Abstract : Biotin‐thiamine responsive basal ganglia disease is an inborn error of metabolism caused by mutations in SLC19A3, encoding a transporter of thiamine across the plasma membrane. We report a novel mutation identified in the homozygous state in a patient with typical brain MRI changes. In addition, this patient had markedly elevated CSF pyruvate, a low lactate‐to‐pyruvate molar ratio, and an abnormal pyruvate peak at 2.4 ppm on brain magnetic resonance spectroscopy. Using aggregated exome sequencing data, we calculate the carrier frequency of mutations in SLC19A3 as 1 in 232 individuals in the general population, for an estimated prevalence of the disease of approximately 1 in 215, 000 individuals. The disease is thus more frequent than previously recognized, and the presence of a pyruvate peak on spectroscopy could serve as an important diagnostic clue.